2013
DOI: 10.1177/0969141313511591
|View full text |Cite
|
Sign up to set email alerts
|

Pre-polysomnographic assessment using the Pittsburgh Sleep Quality Index questionnaire is not useful in identifying people at higher risk for obstructive sleep apnea

Abstract: The PSQI score is not helpful in the pre-polysomnographic assessment of people with suspected OSAS. Further studies are required to provide reliable pre-clinical instruments targeting patients amenable to polysomnography.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0
5

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 35 publications
(23 citation statements)
references
References 27 publications
2
16
0
5
Order By: Relevance
“…To optimize the sensitivity-specificity balance, the cut-off scores were as follows: five for students (sensitivity 72%, specificity 54.5%) [46]; >6 for middle age adults with low back pain (sensitivity ¼ 100%, specificity ¼ 49%) [47]; !8 in post-acute adults with TBI of varying severities (sensitivity 83%, specificity ¼ 100%) [80]. Scarlata et al reported that the PSQI global score !5 was able to differentiate patients with obstructive sleep apnea syndrome diagnoses in a consecutive sample of adults at high risk for the syndrome (sensitivity ¼ 69.7%, specificity ¼ 31%) [75].…”
Section: Cut-off Scoresmentioning
confidence: 99%
“…To optimize the sensitivity-specificity balance, the cut-off scores were as follows: five for students (sensitivity 72%, specificity 54.5%) [46]; >6 for middle age adults with low back pain (sensitivity ¼ 100%, specificity ¼ 49%) [47]; !8 in post-acute adults with TBI of varying severities (sensitivity 83%, specificity ¼ 100%) [80]. Scarlata et al reported that the PSQI global score !5 was able to differentiate patients with obstructive sleep apnea syndrome diagnoses in a consecutive sample of adults at high risk for the syndrome (sensitivity ¼ 69.7%, specificity ¼ 31%) [75].…”
Section: Cut-off Scoresmentioning
confidence: 99%
“…Accordingly, any effort should be made to detect and treat it as soon as possible. Unfortunately, the questionnaires commonly used to select people amenable to polisomnography do not reach a good diagnostic accuracy [107]. As a consequence, many subjects undergo a useless, time-consuming and costly examination.…”
Section: Potential Future Applicationsmentioning
confidence: 99%
“…15,[17][18][19][20][21][22][23][24][25] Additionally, the PSQI has been used in a multitude of settings, including outpatient clinics and inpatient wards, specialty sleep clinics, and primary care offices. 15,26,27 At study enrollment (shortly following inpatient acute rehabilitation admission), participants completed the PSQI regarding their sleep for the 1-month period "before their recent illness." This pre-illness PSQI was intended to describe their sleep quality prior to the events that led to hospitalization and ultimately the post-acute inpatient rehabilitation stay.…”
Section: Sleep Measuresmentioning
confidence: 99%